Metformin attenuates high-fat diet induced metabolic syndrome related osteoarthritis through inhibition of prostaglandins - Liu, Xiaonan; Guo, Qiaoyue; Wang, Lei; Gu, Yiru; Meng, Senxiong; Gu, Yuan; Yu, Bin (Frontiers in Cell and Developmental Biology, 2023)
High-fat diet induces bone marrow inflammation and osteoarthritis phenotype in knee joint, but the underlying mechanisms is unknown. Here, we report that high-fat diet induces aberrant bone formation and cartilage degeneration in knee joint. Mechanistically, a high-fat diet increases the number of macrophages and the secretion of prostaglandins in subchondral bone, promoting bone formation. Metformin treatment is able to decrease the number of macrophages and also the level of prostaglandins induced by high-fat diet in subchondral bone. Importantly, metformin rescues aberrant bone formation and cartilage lesions by decreasing the number of osteoprogenitors and type-H vessels, which also results in relief of osteoarthritis pain response. Thus, we demonstrate prostaglandins secreted by macrophages may be a key reason for high-fat diet induced aberrant bone formation and metformin is a promising therapy for high-fat diet induced osteoarthritis.